2019
DOI: 10.1038/s41593-018-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

Increased synapse elimination by microglia in schizophrenia patient-derived models of synaptic pruning

Abstract: Synapse density is reduced in postmortem cortical tissue from schizophrenia patients, which is suggestive of increased synapse elimination. Using a reprogrammed in vitro model of microglia-mediated synapse engulfment, we demonstrate increased synapse elimination in patient-derived neural cultures and isolated synaptosomes. This excessive synaptic pruning reflects abnormalities in both microglia-like cells and synaptic structures. Further, we find that schizophrenia risk-associated variants within the human com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

45
525
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 576 publications
(574 citation statements)
references
References 65 publications
45
525
1
3
Order By: Relevance
“…Such remodeling of neuronal synapses occurs constantly throughout life (Wu et al, 2015), with synaptic connections in many areas constantly undergoing remodeling based on experience, resulting in synaptic plasticity (Tremblay et al, 2010). Connectivity-refinement deficits may lead to the impairment of brain wiring as implicated in the etiology of several neurodevelopmental disorders (Sekar et al, 2016;Thion, Ginhoux, & Garel, 2018;Zhan et al, 2014), including ASD (Filipello et al, 2018) (Sellgren et al, 2019). Excessive synaptic pruning was shown to occur in this subject-derived cellular model (Sellgren et al, 2019).…”
Section: Microglial Fine Sculpting Of Neuronal Connections During Dmentioning
confidence: 90%
See 3 more Smart Citations
“…Such remodeling of neuronal synapses occurs constantly throughout life (Wu et al, 2015), with synaptic connections in many areas constantly undergoing remodeling based on experience, resulting in synaptic plasticity (Tremblay et al, 2010). Connectivity-refinement deficits may lead to the impairment of brain wiring as implicated in the etiology of several neurodevelopmental disorders (Sekar et al, 2016;Thion, Ginhoux, & Garel, 2018;Zhan et al, 2014), including ASD (Filipello et al, 2018) (Sellgren et al, 2019). Excessive synaptic pruning was shown to occur in this subject-derived cellular model (Sellgren et al, 2019).…”
Section: Microglial Fine Sculpting Of Neuronal Connections During Dmentioning
confidence: 90%
“…Connectivity‐refinement deficits may lead to the impairment of brain wiring as implicated in the etiology of several neurodevelopmental disorders (Sekar et al, ; Thion, Ginhoux, & Garel, ; Zhan et al, ), including ASD (Filipello et al, ) and schizophrenia (McGlashan & Hoffman, ) (Figure ). A recent study utilized microglia‐like cells through cellular reprogramming of monocytes from schizophrenia subjects (Sellgren et al, ). Excessive synaptic pruning was shown to occur in this subject‐derived cellular model (Sellgren et al, ).…”
Section: Microglia Neuron and Ol Crosstalk Under Homeostatic Conditmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice lacking copies of C4 showed fewer synaptic inputs in a visual circuit that normally undergoes synaptic pruning, experimentally validating the functional impact of these associations. Adding further causal evidence, a recent study replicated this pruning effect in human cells using patient‐derived human neural cultures, and even showed that this mechanism of pathology can be targeted therapeutically . These studies explain a small yet important part of the causal pathophysiology, including cell types and biological processes, that lead to risk for schizophrenia, and are particularly exciting as until this point there had been no causal pathophysiology identified for this complex disorder.…”
Section: A Causal Pathway By Which Genetic Variation Impacts Risk Formentioning
confidence: 94%